RANCANGAN MODEL PENGEMBANGAN DESA WISATA SANGEH BERBASIS POTENSI DESA MENUJU PARIWISATA BERKELANJUTAN - Bagus Rendra Maha Putera, Dewa; Herny Susanti, Putu; Eka Wirawan, Putu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The disparity in tourism development in Badung Regency, particularly between the southern and northern regions, highlights the urgency for sustainable and inclusive rural tourism development strategies. This study aims to analyze the potential, challenges, and development strategies of Sangeh Tourism Village as a model of sustainable cultural tourism. A qualitative descriptive method with a case study approach was employed, involving in-depth interviews, focus group discussions (FGDs), participatory observation, and document analysis with tourism village managers, local communities, MSME actors, and tourists. The research instruments were designed to explore aspects such as tourist attractions, community capacity, supporting infrastructure, and institutional governance. The analysis was carried out using the 4A framework (Attraction, Amenity, Accessibility, Ancillary) and SWOT analysis to formulate appropriate development strategies. The findings indicate that Sangeh Village has high potential in ecotourism and cultural tourism, but faces several challenges related to governance, information facilities, and digital literacy. The proposed strategies include optimizing digital promotion, strengthening the role of village-owned enterprises (BUMDes), developing thematic tourism packages, and increasing community involvement in destination management. The tourism village development model is grounded in sustainability principles that integrate environmental conservation, local economic empowerment, and cultural preservation as efforts to build a competitive and inclusive tourism village.